What is new in catheter use and catheter infection prevention in the ICU. Issue 5 (October 2020) - Buetti, Niccolò; Tabah, Alexis; Timsit, Jean-François; Zingg, Walter
Abstract : Purpose of review: Short-term intravascular catheters are instrumental in the care of critically ill patients. Despite their benefits, they also are potential entries for systemic infections. There is a growing body of literature on catheter use and the prevention of intravascular catheter infections in intensive care. This review highlights major recent contributions to the topic and put them into perspective to recommendations on best practice procedures. Recent findings: Many studies published in the last years have evaluated prevention strategies applying technology and addressing behavior change. Skin disinfection with 2% alcoholic chlorhexidine-gluconate (CHG) and CHG-impregnated dressings are increasingly used in clinical practice. However, the role of universal CHG bathing remains controversial. A number of new and innovative technologies are in development. Recent qualitative research offers new perspectives about behavior change interventions to improve implementation. Summary: Many options for effective intravascular catheter infection prevention are currently available. A number of recent systematic reviews and meta-analyses not only confirmed measures targeting best practice and technology at catheter insertion and catheter care but also challenged interventions, such as CHG bathing. More focus should be put to implementation strategies.